Analysis of selectional preference for grassland ecological compensation methods under the perspective of herders differentiation - Hu, Juanjuan; Liu, Yuchen; Zhang, Xinling; Zhang, Jianjun (Frontiers in Sustainable Food Systems, 2025)
IntroductionExploring herders’ preferences for grassland ecological compensation methods provides a decision-making basis for strengthening the incentive effects of grassland ecological compensation policies.MethodsThe research utilized survey data of 372 herders from three prefecture-level cities in Inner Mongolia, and comprehensively applied grey relational analysis (GRA) and multinomial logit (MNL) model to empirically analyze herders’ selectional preferences for grassland ecological compensation methods and influencing factors from the perspective of herders differentiation.ResultsThe findings revealed: (1) More than two thirds (69.28%) of the herders preferred simple and convenient “financial compensation” in addition to existing forms of compensation; 10.22%, 10.48%, and 11.02% of the herders preferred in-kind compensation, technological compensation, and policy-based compensation, respectively. (2) Compared with individual and livestock operation characteristics, herders’ differentiated behavioral attitudes and family characteristics were more strongly associated with their preferences for compensation methods. (3) Compared with direct financial compensation, herders’ gender and transport distance to the nearest marketplace significantly influenced the choice of in-kind compensation; herders’ age, livestock numbers, grazing area, and dependence on subsidy and reward policies significantly influenced the choice of technological compensation; herders’ gender, age, number of family laborers, level of part-time income, willingness for professional transformation, and perception of the rationality of compensation types significantly influenced the choice of policy-based compensation.DiscussionTo optimize compensation modes for grassland ecological conservation, a “diversified & differentiated” positive incentive system should be constructed according to herders’ preferences and differentiated characteristics in order to facilitate voluntary livestock reduction, meanwhile a negative incentive should be incorporated to constrain herders’ overgrazing behavior.